Efektivitas Media SLD Electrical Diagrams terhadap Hasil Belajar pada Pembelajaran Instalasi Tenaga Listrik - Army Kirana Gusnusa; Dwiprima Elvanny Myori (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2022)
Learning media is one of the important factors in education, therefore the development of learning media is needed in order to achieve educational goals. This research aims to determine whether the Android-based SLD Electrical Diagrams application is effective in improving student learning outcomes in electrical power installation subjects in class XI TITL at SMK Negeri 5 Padang. This type of research is a pre-experimental design with a one-group pretest-posttest research design. The subjects in this research were students of class XI TITL for the academic year 2022/2023. Data collection was carried out using questionnaires and questions, which were validated first by the validator lecturer at the Department of Electrical Engineering, FT UNP. Furthermore, pretest questions were given to students followed by the application of the SLD Electrical Diagrams application to the subject of electrical power installation at KD 3.2. And ended with students being given posttest questions and practicality questionnaires. The pretest and posttest data were analyzed with classical completeness with the result that 90% of the total students passed the KKM and the effect size results stated that the effect of applying the SLD Electrical Diagrams application was 2.3 which was categorized as large. While the practicality questionnaire was analyzed by practicality test with 86% results which were categorized as very practical. It can be concluded that the application of the SLD Electrical Diagrams application in electrical power installation subjects is effective.